Advances in high-Tc grain boundary junctions - Tafuri, F.; Kirtley, J.R.; Lombardi, F.; Medaglia, P.G.; Orgiani, P.; Balestrino, G. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2004)
We review results on two novel types of grain boundary Josephson junctions in the high critical
temperature cuprate superconductors. The quality of YBa₂Cu₃O₇-δ biepitaxial grain boundary
Josephson junctions have been improved using a new growth geometry to the point that «tunnel-
like» characteristics are reproducibly obtained. The consequent low barrier transmission probabilities
are apparently favourable to isolate intrinsic d-wave induced effects. We also focus on peculiar
aspects of spontaneous currents in HTS Josephson junctions, which are unique and reflect
the intimate relation between vortex matter and the Josephson effect. Bicrystal grain boundary
Josephson junctions have also been fabricated using artificial superlattice films with as few as six
superconducting copper–oxygen planes. Extrinsic and intrinsic d-wave effects in these junctions
are discussed within the framework of novel designs for π-circuitry and qubits.